Pengaruh Patient Safety Terhadap Patient Experience Di RSUD Kota Makassar - Andi Niartiningsih; Nurul Hidayah Nur; Mene Paradilla; Nurfitriani Nurfitriani; Muhammad Takwa (Pusat riset dan Inovasi Nasional, 2024)
Patient experience is a top priority for healthcare providers with regard to clinical quality, cost reduction and many other issues. This research aims to analyze the influence of patient safety on patient experience at RSUD Makassar City. This type of research is quantitative research using observational research with a cross sectional study design. The sample in this study were inpatient installation totaling 100 patient respondents. The research results show that there is an influence of patient safety on patient experience. It is recommended that the management or patient safety committee of the hospital be expected to carry out regular evaluations and monitoring of the implementation of patient safety targets at the Makassar City Regional Hospital to instill a culture among staff so that patient safety can become a culture that continues to be carried out by all staff.